My Rendezvous with Technology - Devi, K. Aruna; Devi, K. Aruna (International Journal of Psychosocial Rehabilitation, 2020)
My rendezvous with technology started way back in 2012, but till March 2020, I had not made much progress. Starting from March 2020, I have been gearing myself up, to face the challenges of technology and I believe my observations worth recording. Student reaction for this online instruction was quite unexpected. Student attrition was less, as the learners were excited by self-paced learning, that caters to their varied learning styles. The teacher also could achieve the desired learning outcomes more effectively and manage a large class with ease. This enables achieving the futuristic skills of teaching the millennial learners.